2021
DOI: 10.1055/s-0041-1739254
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Management of Pattern Hair Loss

Abstract: Pattern hair loss (PHL) is a condition that worsens with time and the only way it can be slowed down is with pharmacological intervention. Pharmacological treatments for PHL, from an evidenced-based perspective with respect to safety and efficacy, are limited to only two drugs, minoxidil and finasteride. However, there are a host of drugs being used, off-label with limited evidence. This article attempts to review the literature on this topic, and the authors add to this, with their experience of over two deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 108 publications
0
1
0
Order By: Relevance
“…MNX was initially developed as an antihypertensive agent, and its effect on increasing blood flow has been suggested as a mechanism for accelerating hair growth. Other mechanisms have since been proposed, including potassium channel opening 28 , β-catenin signaling activation 29 , extracellular signal-regulated kinase and Akt signaling activation 30 , and increased release of growth factors such as FGF7 and IGF1 31 , 32 . In the present study, MNX treatment upregulated the expression of growth factors, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MNX was initially developed as an antihypertensive agent, and its effect on increasing blood flow has been suggested as a mechanism for accelerating hair growth. Other mechanisms have since been proposed, including potassium channel opening 28 , β-catenin signaling activation 29 , extracellular signal-regulated kinase and Akt signaling activation 30 , and increased release of growth factors such as FGF7 and IGF1 31 , 32 . In the present study, MNX treatment upregulated the expression of growth factors, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Albeit expert consensus conferences generated guidelines, 11 we found no formal guidance on methods for quantification of hair production and how to challenge questionable hypotheses like "regrowth of terminal hair from miniaturized follicles". 12 Published studies clearly illustrate shortcomings in terms of standardization of scalp preparation, hair growth parameters, and global imaging [13][14][15] with low-quality images supporting efficacy claims in the patent literature. 16 In the meantime, developments and innovations in hard and software imaging continue to progress.…”
Section: Introductionmentioning
confidence: 87%
“…Topical minoxidil and finasteride are the two FDA-approved therapies for pattern baldness. Both take at least a 4-to 6-month trial period before showing results, and constant use is necessary to sustain a reaction [19] .…”
Section:  Treatmentmentioning
confidence: 99%